Ninotchka [videorecording (DVD)] - Lubitsch, Ernst, 1892-1947; Garbo, Greta, 1905-1990; Douglas, Melvyn; Claire, Ina, 1893-1985; Lengyel, Menyhért, 1880-1974 (Turner Entertainment Co. ; Warner Home Video, 2005)
Garbo plays a dour, severe Soviet official who comes to Paris on business involving the sale of some czarist jewels. But soon business turns to pleasure as she discovers the special magic of Paris and finds herself succumbing to the charms of a suave Frenchman named Leon D'Algout (Melvyn Douglas). The plot bubbles merrily as Ninotchka chooses between romance and duty--and must even confront a rival for Leon's affection in the exiled Grand Duchess Swana (Ina Claire).